RETROSPECTIVE AND CURRENT LEVELS OF SELF-EFFICACY IN JAPANESE LEARNERS - Burrows, Lance Paul (Indonesian Journal of Applied Linguistics, 2016)
Self-efficacy is the strength of expectations individuals maintain about their ability to successfully perform a behavior. As such, researchers from many fields (e.g., educational psychology, health, medicine) have employed self-efficacy to predict and describe a wide range of human functioning. However, relatively few studies in second language (L2) reading have investigated the relationship between reading self-efficacy and proficiency, and those that have tend to suffer from design flaws and/or problems with analyses. Furthermore, no studies have explored the effects that past experiences seem to have on current levels of reading self-efficacy. In order to address this lack of empirical research, this quasi-experimental study was conducted to investigate how participants’ retrospective ratings of reading self-efficacy related to current levels, and how those current levels, in turn, relate to reading proficiency. The participants, all of whom were non-English majors, consisted of 322 first- and second-year Japanese university students, ages 18 to 20. Data to examine retrospective self-efficacy was collected through the sources of reading self-efficacy questionnaire and TOEIC reading scores were utilized for the reading proficiency variable. The results suggest that the retrospective ratings of self-efficacy in junior high and high school are closely related to the participants’ current levels of reading self-efficacy. The results from an ANOVA also showed a statistically significant difference in reading performance between those with high reading selfefficacy and those with low reading self-efficacy. The results demonstrate how important past levels of self-efficacy can be on learners’ current levels of self-efficacy; therefore providing students in the EFL classroom with achievable activities and opportunities to cultivate their self-efficacy would be indicated. Further research is necessary to determine specific ways in which teachers may help foster a stronger sense of self-efficacy in EFL learners.